Given the function:
![y=\sqrt[]{x}](https://img.qammunity.org/2023/formulas/mathematics/college/z3kevgn2c29nk34ba6n3a5xhvm9rhyzg0b.png)
we will find the function that results from the following transformations:
(1) Shift down 7 units
so, the result will be:
![y=\sqrt[]{x}-7](https://img.qammunity.org/2023/formulas/mathematics/college/mdr0yw022o7cqt95zf5chfi6u1p86nbjhd.png)
(2) Reflect on the x-axis
so, the rule of reflection will be: (x,y) →(x, -y)
so, the function will be:
![y=-\sqrt[]{x}+7](https://img.qammunity.org/2023/formulas/mathematics/college/32r91o4de498do9i3t2fivquskwecdsb33.png)
(3) Reflect on the y-axis
so, the rule of reflection will be: (x,y) →(-x, y)
So, the function will be:
![y=-\sqrt[]{-x}+7](https://img.qammunity.org/2023/formulas/mathematics/college/rlq64f82pwx02436rfyhwu772s458jjpud.png)